2018
DOI: 10.1021/acs.langmuir.8b01602
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Polyampholytes as Macromolecular Cryoprotective Agents

Abstract: A series of polyampholytes based on different molar ratios on N, N-dimethylaminopropyl methacrylamide (DMAPMA), acrylic acid (AA), and optionally, N- tert-butylacrylamide ( t-BuAAm), were prepared by free radical copolymerization, and tested as DMSO-free cryoprotective agents for 3T3 fibroblast cells by using a standard freeze-rethaw protocol. Polybetaines prepared by reaction of DMAPMA homo and copolymers with 1,3-propane sultone were used as additional controls. Results showed strong effects of copolymer com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 63 publications
1
60
0
Order By: Relevance
“…Polyampholytes have also been reported to cryopreserve cells by strongly interacting with the cell membrane, with hydrophobicity increasing the cytoprotective effect by increasing both the affinity for membrane interaction and affinity for ice recrystallization inhibition [ 19 ]. This type of NPA can be of either synthetic [ 19 , 20 ] or semisynthetic nature, such as carboxylated ε-poly-ʟ-lysine polymers [ 18 ] that have successfully been implemented into the cryopreserved human mesenchymal stem cells and induced pluripotent stem cells. In addition, temperature-responsive physical gels and zwitterionic polymers have been used in the cryoprotection of 3D cell cultures in which these materials can act at the same time as the 3D scaffolds and CPA in the composite cell system [ 21 ].…”
Section: The Cryopreservation Process and The Role Of Cpamentioning
confidence: 99%
“…Polyampholytes have also been reported to cryopreserve cells by strongly interacting with the cell membrane, with hydrophobicity increasing the cytoprotective effect by increasing both the affinity for membrane interaction and affinity for ice recrystallization inhibition [ 19 ]. This type of NPA can be of either synthetic [ 19 , 20 ] or semisynthetic nature, such as carboxylated ε-poly-ʟ-lysine polymers [ 18 ] that have successfully been implemented into the cryopreserved human mesenchymal stem cells and induced pluripotent stem cells. In addition, temperature-responsive physical gels and zwitterionic polymers have been used in the cryoprotection of 3D cell cultures in which these materials can act at the same time as the 3D scaffolds and CPA in the composite cell system [ 21 ].…”
Section: The Cryopreservation Process and The Role Of Cpamentioning
confidence: 99%
“…However, the majority of cells died after 24 h in culture. 17 Similarly, Naaldijk et al reported immediate post-thaw viabilities of MSC frozen with DMSO and hydroxyethyl starch to be ∼85%, but this plummeted to <30% after 3 days in culture for samples containing <4% DMSO. 24 These studies highlight that immediate post-thaw viability is not a good predictor of cell health.…”
mentioning
confidence: 97%
“…Even when cell viability is excellent just after thawing the cells, the final cell recovery can be low . The post-thaw growth rate of 3T3 fibroblast cells was significantly suppressed, even though immediate post-thaw cell viability was as good as 70 to 90% when using cryoprotecting polyampholytes consisting of N , N -dimethylaminopropyl methacryl amide and acrylic acid . In addition, cell adhesion and long-term cell viability were poor.…”
Section: Resultsmentioning
confidence: 99%
“…57 The post-thaw growth rate of 3T3 fibroblast cells was significantly suppressed, even though immediate post-thaw cell viability was as good as 70 to 90% when using cryoprotecting polyampholytes consisting of N,N-dimethylaminopropyl methacryl amide and acrylic acid. 58 In addition, cell adhesion and long-term cell viability were poor. A similar trend was observed for carboxylated poly(L-lysine) for cryopreservation of human mesenchymal stem cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%